Inter Tester Reliability of Fitmust Hand Held Dynamometer among Healthy Participants - S.J., Kanimozhiselvi; M., Sindhuja; J., Radhika (INTI International University, 2023)
Background: Strength testing is one of the primary assessment tools for physical strength examination, and an increase in strength is the aim of many rehabilitation programs. Manual muscle testing (MMT) is the most commonly used strength testing method in clinical settings. It is a subjective measurement technique whereby the tester applies resistance to a maximum voluntary muscle contraction. The reliability of the Fitmust hand-held dynamometer is not previously reported in the literature. Aims and Objectives: The study aims to test the reliability of the Fitmust hand-held dynamometer for lower limb muscles in comparison with the Jamar Hand Held dynamometer. Methods: Maximum voluntary isometric contraction of hip extension, knee extension, and plantar flexion is measured by two different therapists on different days using fit must hand-held dynamometer for 40 healthy participants of age category 18- 30 years. Result: Reliability was evaluated by computing Intra-class Correlation Coefficients (ICC), which analyse the consistency between two or more quantitative measures, and Cronbach's Alpha which measured agreement. Conclusion: Inter-tester reliability data obtained for Assessor 1 and 2 were consistent for knee measurements. However, data for the hip and ankle varied considerably. Assessors 1 and 2 demonstrated a 'moderate to excellent' association for knee Measurements.